Developing Crispy Jelly Products from Ginger and Pumpkins and Fostering an Innovation Community in Ban So Community, Phayao Province, Thailand - Sathientharadol, Phitsinee; Duangfai, Chanapa; Chaibao, Jaroon; Kamchompoo, Suleeporn (Area Based Development Research Journal, 2024)
Ban So Community, Mae Na Rua Subdistrict, Mueang District, Phayao Province, Thailand is an agricultural community where 70% of the population cultivates ginger and pumpkins as the main economic crops. The community has been affected by the low market prices of ginger and pumpkins due to oversupply and limited income sources. 6 housewives and 3 juveniles participated in a participatory learning process through problem analysis, product development, and distribution, including 1) analysis of the strengths and weaknesses of instant ginger powder and pumpkin crisp; 2) determination of target market groups; 3) specification of new products; 4) experimental production of crispy ginger jelly and crispy pumpkin jelly; 5) determination of size and packaging design; 6) analysis of nutritional information and preservation; 7) pricing determination; 8) market testing; 9) product improvement; 10) trial sales and development of distribution channels and promotion; 11) formulation of sales promotion strategies; 12) product distribution; and 13) becoming ‘an innovation community’. This process empowered the housewives to produce crispy ginger jelly and crispy pumpkin jelly as their second job and generate an additional income of 7,990 Baht (around 234 USD) in 3 months. The crispy ginger and pumpkin jellies could increase the value of ginger and pumpkins from 20-30 Baht to 350 Baht (from 0.58-0.88 USD to 10.23 USD) per kilogram. Moreover, the participatory learning process has led to the emergence of 3 community innovators in developing crispy ginger jelly and crispy pumpkin jelly who can further their knowledge of crispy jelly production from Spring Bitter Cucumber and Clitoria ternatea. Furthermore, they can transfer production and distribution methods to the juveniles and those who are interested in them, which is a factor in the sustainability of the production and distribution of crispy jelly products in the future.